2007
DOI: 10.1111/j.1365-2869.2007.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal sleep, daytime sleepiness, and napping among women with significant emotional/behavioral premenstrual symptoms

Abstract: SUMMARY The objective of this study is to examine daytime sleepiness and alertness and nap characteristics among women with significant emotional ⁄ behavioral premenstrual symptoms, and to determine their relationship with nocturnal sleep. Participants spent one night during the follicular phase and two nights during the late-luteal phase, one of which occurred after a 40 min opportunity to nap, sleeping in the laboratory. Subjective measures of sleepiness and alertness were completed during the afternoon of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…[11] Similar results were shown in a study by Lamarche and colleagues who found decreased SWS and REM sleep and increased stage 2 sleep during the LP in both healthy and women with PMS. [35] A reduction in REM sleep during LP compared to FP has also been reported by Shechter and colleagues who observed this variation in healthy women and patients with PMDD. [36] Similarly, in their sleep EEG study Parry and colleagues examined eight women with moderate to severe premenstrual depression and eight controls, two nights per week over the course of one menstrual cycle and found that depressed women had more stage 2 sleep and less REM sleep than controls.…”
Section: Pmdd and Sleep Qualitymentioning
confidence: 69%
“…[11] Similar results were shown in a study by Lamarche and colleagues who found decreased SWS and REM sleep and increased stage 2 sleep during the LP in both healthy and women with PMS. [35] A reduction in REM sleep during LP compared to FP has also been reported by Shechter and colleagues who observed this variation in healthy women and patients with PMDD. [36] Similarly, in their sleep EEG study Parry and colleagues examined eight women with moderate to severe premenstrual depression and eight controls, two nights per week over the course of one menstrual cycle and found that depressed women had more stage 2 sleep and less REM sleep than controls.…”
Section: Pmdd and Sleep Qualitymentioning
confidence: 69%
“…The most consistently observed menstrual cycle-related changes in the sleep profile of healthy women are a reduction of REM sleep [49, 5153, 56], with a maintenance of homeostatic sleep mechanisms throughout the cycle [90], and a robust variation of SFA across the menstrual cycle [48, 49, 55], which increases in association with progesterone during the LP. Similarly, women with PMS/PMDD have also shown decreases in REM sleep [52, 56] and increases in SFA [55] during the LP compared to the FP.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that, compared to controls, PMS patients had more stage 2 sleep (%) and less REM sleep (%), and within these patients, stage 3 sleep (min; peaks near the late-FP/early-LP) and intermittent awakenings (peaks near the late-LP) varied significantly across the menstrual cycle [45]. More recently, a study including healthy women and those with PMS found decreased SWS (%) and REM sleep (%) as well as increased stage 2 (%) during the LP in both groups [56]. …”
Section: Sleep Across the Menstrual Cycle In Pmdd Womenmentioning
confidence: 99%
“…The National Sleep Foundation Sleep in America survey (2007) identified that 25%–33% of menstruating women complained of sleep disturbances during the premenstrual week or during menses; women who reported severe premenstrual symptoms (PMS) also experienced symptoms of insomnia and daytime sleepiness 6 . Smaller studies of women with premenstrual mood disorders have identified substantial sleep disturbances, including either hypersomnia or insomnia during the premenstrual period 89 . The extent to which findings from these studies can be extrapolated to midlife women as they approach menopause remains in question, thereby limiting our understanding of the extent to which increased sleep disturbances in midlife women are associated with alterations in menstrual cycles and hormone dynamics 4, 10 .…”
Section: Introductionmentioning
confidence: 99%